Eocene‐Oligocene proto‐Cascades topography revealed by clumped (Δ47) and oxygen isotope (δ18O) geochemistry (Chumstick Basin, WA, USA). Issue 3 (6th March 2016) - Methner, Katharina; Fiebig, Jens; Wacker, Ulrike; Umhoefer, Paul; Chamberlain, C. Page; Mulch, Andreas
Abstract: The topography of the present‐day Washington Cascades impacts atmospheric circulation and precipitation patterns in the Pacific Northwest, introducing a pronounced orographic rain shadow in the lee of the mountain range. The temporal development of Cascade topography, however, remains largely unconstrained for the early Cenozoic. Based on coupled carbonate clumped isotope (Δ47 ) and oxygen isotope (δ 18 O) measurements we reconstruct δ 18 O values of Eocene groundwater (δ 18 Owater ) in the Chumstick basin (central Washington), today located in the Cascade rain shadow. Δ47 (paleo)thermometry indicates a systematic change in basin burial temperatures from 110°C to 70°C depending on burial depth in the basin. These data are in good agreement with low‐ T thermochronological and vitrinite reflectance data, and further constrain the basin burial and exhumation history. In concert with field observations, microstructural analysis, and δ 18 O values of the analyzed carbonates, we suggest that the Δ47 temperatures and δ 18 O values reflect open‐system carbonate cement recrystallization in meteoric‐derived groundwaters during early burial diagenesis. Assuming open‐system behavior, reconstructed mean δ 18 Owater values of −7‰ (middle Eocene) to −9‰ (late Eocene/early Oligocene) are consistent with a low‐elevation origin of the corresponding meteoric waters that permeated the sandstone/conglomerate members of the Eocene sedimentary units. In light of the paleogeographic setting of the Chumstick basin, the reconstructed δ 18 Owater values agree well with Pacific‐derived moisture that did not experience strong rainout. The absence of a rain shadow effect therefore permits only moderate Eocene/Oligocene elevations at least for the southern part of the Washington proto‐Cascades. Key Points: Combined clumped and stable isotope data permit reconstruction of basin fluids Oxygen isotopes indicate absence of Eo‐/Oligocene Cascades rain shadow Clumped isotopes record diagenetic conditions during basin burial